2021
DOI: 10.1002/epi4.12463
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and cerebrospinal fluid immune and complement activation in Ugandan children and adolescents with long‐standing nodding syndrome: A case‐control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…In a previous study, higher levels of MCP-1 were found in brain tissue of patients with intractable epilepsy [ 57 ]. However, the findings are not comparable to the results of the study by Ogwang et al [ 58 ], in which decreased concentrations of MCP-1 were detected in plasma samples of nodding syndrome individuals compared to healthy controls. The different outcome of the measurements could be due to differences in patient inclusion; their study included individuals with nodding syndrome based on the presence of OV-16 antibodies, a marker for exposure to O .…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous study, higher levels of MCP-1 were found in brain tissue of patients with intractable epilepsy [ 57 ]. However, the findings are not comparable to the results of the study by Ogwang et al [ 58 ], in which decreased concentrations of MCP-1 were detected in plasma samples of nodding syndrome individuals compared to healthy controls. The different outcome of the measurements could be due to differences in patient inclusion; their study included individuals with nodding syndrome based on the presence of OV-16 antibodies, a marker for exposure to O .…”
Section: Discussioncontrasting
confidence: 99%
“…NS has emerged in areas of hyper-endemicity for onchocerciasis (also known as river blindness), hence the interest in Onchocerca volvulus (OV). Six case-control studies have been conducted in Southern Sudan and Uganda and report a positive and significant association between onchocerciasis and NS [13][14][15][16][17][18]. The risk associated with onchocerciasis varies according to study areas and also to the tests used (Table 2).…”
Section: Associated Factors and Pathophysiology Of Ns Parasitic Infec...mentioning
confidence: 99%
“…These two post-mortem studies were not assessed by the NOS and were of fair quality according to the DCP scale. In addition, results from a study of good NOS quality and fair DCP quality suggest a possible role for central nervous system complement activation in the pathogenesis of chronic NS [16].…”
Section: Geneticsmentioning
confidence: 99%
“…The symptoms develop in early childhood, and patients progressively develop neurocognitive and physical impairment [1]. It has been suggested that NS is one of the clinical presentations of onchocerciasis-associated epilepsy (OAE) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%